Analysis of the Relationship between the Use of Hypertension Services in Achieving Minimum Service Standards (SPM) in the Community on Barrang Caddi Island - St. Rosmanely; Nasrah; M. Nabil Sakti Pahruddin; Yuana Wira Dwi Satya Ilham Putra; Eva Arista (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Based on Makassar City health profile data in 2021, there are still several health service and management criteria that have not achieved the SPM targets for Health Sector or SDG's. At the Barrang Lompoa Community Health Center, the SPM achievement related to patients receiving health services who suffer from hypertension in 2021 is 46.2%. This achievement still does not meet the target that has been set, namely 100%. Objective: To find out the factors that influence the use of hypertension services in the community at Pustu Barrang Caddi in 2024. Methode: The type of research used is Cross Sectional Study. This research was conducted on Barrang Caddi Island, Makassar City in March - April 2024. The population in this study was 351 households. The sample in this study was part of the population on Barrang Caddi Island, that is 188 households. Result: The results of data analysis include univariate analysis with frequency distribution and bivariate chi-square test. Data analysis was carried out bivariately using the Chi-Square test with a significance level of 5% (?=0.05). The influence of age (p=0.890), education (p=0.980), employment (p=1.000), and access (p=0.577), from Chi-Square results found a relationship between factors on the utilization of hypertension services at Pustu Barrang Caddi in 2024.